Parent and Child Reports of Parenting Behaviors: Agreement Among a Longitudinal Study of Drug Court Participants - Guastaferro, Kate; Osborne, Melissa C.; Lai, Betty S.; Aubé, Samantha S.; Guastaferro, Wendy P.; Whitaker, Daniel J. (Frontiers in Psychiatry, 2021)
Identifying ways to support children of parents with substance use disorder is a critical public health issue. This study focused on the parent-child relationship as a critical catalyst in child resilience. Using data from a longitudinal cohort study, the aims of this study were to: (1) examine the agreement between parent and child reports of parenting behaviors and (2) describe the association between agreement and child mental health. Participants were 50 parent-child dyads that included parents enrolled in an adult drug court and their children, aged 8-18. Overall, agreement (i.e., concordance) between parent and child reports of parenting was slight to fair. Parents reported their parenting behaviors to be slightly more positive than how children rated the same behaviors in the areas of: involvement, 0.53 (SD=0.80); positive parenting, 0.66 (SD=0.87), and monitoring behaviors, 0.46 (SD=0.90). Parents also rated themselves, in comparison to their children’s reports, as using less inconsistent discipline, -0.33 (SD=1.00), and less corporal punishment, 0.13 (SD=1.01). Agreement was related to some, but not all, child mental health outcomes. When parents rating their parenting as more positive than their child reported, that had a negative effect on child self-esteem and personal adjustment. Contrary to hypotheses, we did not find a significant relationship between positive parenting and internalizing problems. Findings have implications for obtaining parent and child reports of parenting within the drug court system, and for identifying children at higher risk for externalizing problems.